Quantification of water penetration through cracked concrete walls by an idealized experimental set-up using local parameters - Salison, Arse John P.; Tejuco, Maria Karen Joy C.
The weather condition of the Philippines and tbe susceptibility of concrete wall panels to cracking condition make water penetration throngh cracks an occurring problem in building envelope durability. This experiment aims to develop a suitable testing apparatus for water penetration on cracked concrete walls and characterize the behavior of water penetration by direct measurement of water through simulated cracks under varying weather condition. The main output of the experiment would be a set of graphs showing moisture penetration time vs. crack width, moisture penetration time vs. rain intensity, quantity of water penetration vs. crack width and quantity of water penetration vs. rain intensity. It was found that as the flow of tbe wind driven rain and the average pressure increases, the volume of water penetration increases while the time of water penetration increases. For this research, the limiting crack width was found to be 1-mm, where in when that is reached, the volume of water penetration struts to decrease while the time of water penetration starts to become constant. This behaviour happens because when the crack width is large enough (> 1-mm), the water does not completely fill the space along the crack depth, therefore the pressure is no longer the dominant driving force.